PERAN TRANSFORMATIONAL LEADERSHIP DALAM ORGANIZATIONAL LEARNING: LITERATURE REVIEW - Eliza Ariesta; Rawit Sartika (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This paper aims to investigate how the relationship between Transformationalleadership style and learning organization (OL))/learning organization(LO)/learning organization (OL) is measured in the literature. This systematicliterature review analyzes peer-reviewed publications. English which examinesthe relationship between leadership and Organizational Learning (OL)empirically. A total of 27 articles have been found in 42 journals. This paperprovides a holistic view of transformational leadership that has been linked toOrganizational Learning (OL) in various countries and industries. Researchmethods from the literature were also examined.